2023
DOI: 10.3389/fmicb.2023.1079187
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia sabiae administration alters zebrafish anxiety-like behavior via gut microbial taurine metabolism

Abstract: Interventions to the gut microbiome manipulate the gut–brain axis and could be useful in the treatment of anxiety and depression. In this study, we demonstrated that administration of the bacterium Paraburkholderia sabiae reduces anxiety-like behavior in adult zebrafish. P. sabiae administration increased the diversity of the zebrafish gut microbiome. Linear discriminant analysis Effect Size (LEfSe) analysis revealed that the populations of Actinomycetales including Nocardiaceae, Nocardia, Gordoniaceae, Gordon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…More recently, administration of Lactobacillus delbrueckii by direct inoculation into fish tanks resulted in reduced anxiety-like behavior in adult female zebrafish, altering its gut and brain transcriptomes (Olorocisimo et al, 2023). A similar study by Ichikawa et al showed that administration of Paraburkholderia sabiae in rearing water reduced anxiety-like behaviors and increased diversity of gut microbiota in adult zebrafish (Ichikawa et al, 2023). In investigation of neural hyperactivity, supplementation with Lactobacillus plantarum HNU082 in the feed influenced select neurotransmitters in adult zebrafish (Zhang et al, 2021b).…”
Section: Zebrafish As a Model To Explore The Microbiota-neural Axismentioning
confidence: 93%
“…More recently, administration of Lactobacillus delbrueckii by direct inoculation into fish tanks resulted in reduced anxiety-like behavior in adult female zebrafish, altering its gut and brain transcriptomes (Olorocisimo et al, 2023). A similar study by Ichikawa et al showed that administration of Paraburkholderia sabiae in rearing water reduced anxiety-like behaviors and increased diversity of gut microbiota in adult zebrafish (Ichikawa et al, 2023). In investigation of neural hyperactivity, supplementation with Lactobacillus plantarum HNU082 in the feed influenced select neurotransmitters in adult zebrafish (Zhang et al, 2021b).…”
Section: Zebrafish As a Model To Explore The Microbiota-neural Axismentioning
confidence: 93%